Discovering Bugs, or Ensuring Success? Finding errors is not the same as making certain a software product works correctly. - Buzruk, Vivek (Communications of the ACM, 2018)
The author discusses the difference between finding computer errors or software testing and ensuring that a computer program or software product works correctly. Topics include the challenge of determining when to stop testing a program as there is no way of verifying all bugs have been found, and the importance of giving testers a goal rather than an unlimited amount of time to continue testing a program.